What's so good about vegetables? - Randall, Ronne (Milwaukee, Wis. : G. Stevens, 2004)
Discusses the nutritional value of various kinds of foods.
What's so good about bread? -- What's so good about vegetables? -- What's so good about fruit? -- What's so good about meat? -- What's so good about milk? -- What's so good about butter? -- What's so good about water? -- Where does my food go?
First published in Great Britain in 2003 by ticktock Media, Tunbridge Wells, Kent, England.
Includes index.
3.9
K-3
Keywords: Diet -- Juvenile literature; Nutrition -- Juvenile literature; Nutrition; Nutrition